IMPLEMENTASI METTODE VIKOR DALAM PENILAIAN KINERJA GURU DI MTS 2 TANGGAMUS - Aini, Zahratul (YHMM PUBLISHING, 2025)
Teacher performance assessment is a crucial component in improving the quality of education and maintaining academic standards in schools. However, manual and detailed assessment processes often lead to subjectivity and potential social jealousy among teachers, which may negatively affect motivation and the teaching environment. This study aims to enhance transparency, objectivity, and efficiency in teacher performance evaluation by applying a Decision Support System using the VIKOR method. The research was conducted at MTs Negeri 2 Tanggamus using a quantitative approach. Data were collected through interviews with the school principal, direct observation of the assessment process, and literature studies. Five assessment criteria were used, namely discipline, teacher attendance, competence, task performance, and responsibility. The VIKOR method was applied to process the normalized decision matrix, calculate the utility measure (S), regret measure (R), and VIKOR index (Q), which were then used to rank teacher performance objectively. The results indicate that the application of the VIKOR method successfully produces a clear and systematic ranking of teacher performance. The findings show that Teacher A achieved the best performance rank, followed by Teacher B and Teacher C. This study concludes that the VIKOR method is effective in reducing subjectivity and supporting fair, data-driven decision-making in teacher performance assessment.